World cassava production and yield trends 1960-1968 = Tendencias de la producción y rendimiento de la yuca - Díaz, R.O. (International Center for Tropical Agriculture, 1972)
Basic data were compiled in table form on cassava production, and an analysis was made of past trends of the relationship cassava production/population for each of the cassava-producing countries from 1960-68. The tendency of per capita production was estimated by simple linear regression. During the period studied, the area planted to cassava increased an av of 200,000 ha/yr; the largest increases were in Africa and S.A. (480 and 124,000 ha, respectively). World production increased 2 million t/yr, but yields did not change. Per capita production increased 7.5 kg/yr in S.A. but decreased for the rest of the world. About 40 percent of world production comes from S.A. (25 percent of the area planted) and 36 percent from Africa (approx 50 percent of the world area). Brazil produces approx 1/3 of the total world production and 85 percent of S.A. production. Av world yield is estimated at 8.69 t/ha; Malawi and Brazil have the highest yields (23 and 20 t/ha, respectively). It is concluded that population growth exceeds the increase in cassava production since there is a decreasing trend in per capita production. (CIAT)